Weight loss of five commercially available denture teeth after toothbrushing with three different dentifrices Perda de massa de cinco marcas de dentes artificiais disponíveis no mercado após escovação com três diferentes dentifrícios - Karina Matthes de Freitas; Helena de Freitas Oliveira Paranhos (University of São Paulo, 2006)
Brushing is the most common cleansing method employed on complete dentures and it may damage the integrity of acrylic resin, the main component of this type of prosthesis. This study evaluated the abrasion resistance of artificial teeth with different number of acrylic layers, and the abrasiveness of specific and non-specific dentifrices for denture cleaning. The abrasion test was conducted by a tooth brushing device, using soft toothbrushes under load (200g). Sixty artificial teeth specimens were manufactured, 12 from each brand: Vipi-Dent Plus (Dental Vipi), Trubyte Biotone (Dentsply), Trilux (Ruthinium), Ivostar (Ivoclar) and SR Vivodent PE (Ivoclar). Three brands of dentifrices were selected: Colgate (Colgate-Palmolive), Bonyplus (Bonyf AG) and Dentu-Creme (Dentco). Distilled water was used as control. The brushing time was 100 minutes, at 356 strokes/minute. The specimens were weighed on an analytical balance before and after the abrasion test. Analysis of dentifrices' abrasive particles was made by scanning electron microscopy (SEM). Two-way ANOVA and Tukey tests were employed (alpha=0.05). The general mean of weight loss values were obtained: 6.1 mg (Ivostar); 6.0 mg (Trilux); 5.9 mg (Trubyte); 5.8 mg (Vipi); 5.3 mg (Vivodent). The abrasiveness difference among teeth brands was not statistically significant. The Colgate dentifrice produced the greatest weight reduction (10.1 mg), followed by Dentu-Creme (7.6 mg). Bonyplus was the least abrasive (2.4 mg), similar to the distilled water used as control group (3.1 mg) (p=0.05). It was concluded that all acrylic teeth presented similar abrasion resistance. Specific dentifrices for dentures tend to cause less damage to acrylic resin. A escovação é o método mais empregado para higienização de próteses totais e pode causar danos à resina acrílica, seu principal componente. Este estudo avaliou a resistência à abrasão de dentes de resina acrílica, com diferentes camadas de prensagem, frente a dentifrícios específicos e não específicos para higienização de dentaduras. O ensaio de abrasão foi realizado utilizando-se uma máquina de escovação, com escovas macias sob carga de 200g. Foram confeccionados 60 corpos-de-prova, 12 de cada marca comercial: Vipi-Dent Plus (Dental Vipi), Trubyte Biotone (Dentsply), Trilux (Ruthinium), Ivostar (Ivoclar), SR Vivodent PE (Ivoclar). Foram empregados os dentifrícios: Colgate (Colgate Palmolive), Bonyplus (Bonyf AG) e Dentu-Creme (Dentco). Água destilada foi utilizada como controle. O tempo de escovação foi 100 minutos, a 356 rotações/minuto. Os corpos-de-prova foram pesados em balança analítica antes e após os ensaios. As partículas abrasivas dos dentifrícios foram analisadas em microscopia eletrônica de varredura (MEV). Os testes ANOVA e Tukey (alfa=0,05) foram empregados. A perda de peso média dos dentes foi: 6,1 mg (Ivostar); 6,0 mg (Trilux); 5,9 mg (Trubyte); 5,8 mg (Vipi); 5,3 mg (Vivodent). Não houve diferença significante entre as marcas de dentes. O dentifrício Colgate causou maior perda de massa (10,1 mg), seguido pelo Dentu-Creme (7,6 mg). O Bonyplus foi o menos abrasivo (3,1 mg), sem diferença estatística em relação ao controle (2,4 mg) (p=0,05). Foi concluído que todos os dentes foram igualmente resistentes à abrasão, independentemente do número de prensagens. Dentifrícios específicos para próteses totais geraram menos danos à superfície acrílica.